Can anyone answer this question pls
Attachments:
Answers
Answered by
1
6√5x² - 9x - 3√5 = 0
6√5x² - 15x - 6x - 3√5 = 0
3√5x(2x - √5) - 3(2x - √5) = 0
(3√5x - 3) (2x - √5) = 0
x = 1/√5 , √5/2
hope it helps
6√5x² - 15x - 6x - 3√5 = 0
3√5x(2x - √5) - 3(2x - √5) = 0
(3√5x - 3) (2x - √5) = 0
x = 1/√5 , √5/2
hope it helps
Harigrandhi:
thanks
Answered by
1
6√5 x2 - 9x-3√5=0
6√5x2-15x+6x-3√5=0
3√5x(2x-√5) +3(2x-√5)=0
(3√5x+√3)(2x-√5)=0
x=√5/2 or -√5/√3
6√5x2-15x+6x-3√5=0
3√5x(2x-√5) +3(2x-√5)=0
(3√5x+√3)(2x-√5)=0
x=√5/2 or -√5/√3
Similar questions